2018
DOI: 10.1093/mnras/sty2438
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of magnetic fields in stars

Abstract: Are the kG-strength magnetic fields observed in young stars a fossil field left over from their formation or are they generated by a dynamo? We use radiation non-ideal magnetohydrodynamics simulations of the gravitational collapse of a rotating, magnetized molecular cloud core over 17 orders of magnitude in density, past the first hydrostatic core to the formation of the second, stellar core, to examine the fossil field hypothesis. Whereas in previous work we found that magnetic fields in excess of 10 kG can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
(86 reference statements)
1
24
0
Order By: Relevance
“…Star formation begins later in the high resolution models, with higher-resolution models collapsing slower than their lowerresolution counterparts (as previously discussed in Wurster et al 2018c). Once the star formation begins in I05 h , the star formation rate is similar to that of I05, and both models have accelerating star formation rates.…”
Section: A2 Stellar Populationsmentioning
confidence: 64%
“…Star formation begins later in the high resolution models, with higher-resolution models collapsing slower than their lowerresolution counterparts (as previously discussed in Wurster et al 2018c). Once the star formation begins in I05 h , the star formation rate is similar to that of I05, and both models have accelerating star formation rates.…”
Section: A2 Stellar Populationsmentioning
confidence: 64%
“…The cloud evolution during the gas collapsing phase was investigated in many past studies (e.g. Banerjee & Pudritz 2006;Machida et al 2006;Tomida et al 2015;Tsukamoto et al 2015;Wurster et al 2018). At first, we overview the driving of outflows in the accreting cloud.…”
Section: Resultsmentioning
confidence: 99%
“…In ideal magnetohydrodynamics (MHD) studies of the formation of an isolated star, magnetic fields of 10 4 − 10 6 G are shown to be implanted in the stellar core at birth (e.g. Machida et al 2006Machida et al , 2007Bate et al 2014;Wurster et al 2018d;Vaytet et al 2018). This magnetic field was much stronger than expected, and largely resulted because ideal MHD was employed.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, however, perform their simulations at various resolutions to understand how resolution affects their results (e.g. Schmidt et al 2010;Federrath 2015;Wurster et al 2016Wurster et al , 2018dCunningham et al 2018;Grudić et al 2021), while several have shown that their results remain unconverged, even when using the highest resolution feasible (e.g. Mac Low et al 1998;Meru & Bate 2011;Joos et al 2013;Bate et al 2014;Hosokawa et al 2016;Haugbølle et al 2018;Meyer et al 2018;Hennebelle 2018), and a few have shown that convergence has been reached (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation